PENGARUH EMPLOYEE ENGAGEMENT, KOMITMEN ORGANISASI, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KESIAPAN UNTUK BERUBAH (READINESS FOR CHANGE) PADA KARYAWAN UNIVERSITAS AHMAD DAHLAN - Efi Astuti; Rikha Muftia Khoirunnisa (Universitas Ahmad Dahlan, 2018)
This study aims to determine the effect of Employee Engagement, Organizational Commitment, and Transformational Leadership on Readiness for Change in employees of Ahmad Dahlan University, Yogyakarta. The population in this study is the employees of Ahmad Dahlan University of Yogyakarta, amounting to 357 people and the sample used is 103 people, the sampling technique used is purposive sampling with sample criteria are permanent employees with a minimum working period of one year and have not moved to campus 4 UAD. The data analysis tool used is multiple linear regression test. The results of this study indicate that Employee Engagement has no effect on Readiness for Change of Ahmad Dahlan University employees. Organizational Commitment affects the Readiness for Change of Ahmad Dahlan University employees. Transformational leadership does not affect the Readiness for Change of Ahmad Dahlan University employees. And employee engagement, organizational commitment, and transformational leadership simultaneously influence the readiness for change in employees of Ahmad Dahlan University Yogyakarta.